PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KREATIVITAS DAN PRESTASI BELAJAR (Studi Pada Pelajaran Kimia Siswa Kelas XII IPA di SMA Negeri 3 Pagaralam) - Eko Prianto (UNIB Press, 2021)
This study aims to describe the application of the problem-based learning model which can effectively increase the creativity and learning achievement of students in class XII IPA 3 SMA Negeri 3 Pagar Alam. The research method used was Classroom Action Research which was followed by a quasi experiment. The research subjects were students of SMA Negeri 3 Pagar Alam with class XII IPA 3 as the PTK class, class XII IPA 2 as the experimental class and class XII IPA 1 as the control class. The technique used for sampling in this study was a random sampling technique by lottery. CAR is done in 3 cycles. Data collection techniques using observation sheets and tests. Data analysis using the average value and t-test. Problem Based Learning is effective and can improve the chemistry learning achievement of students in class XII IPA SMA Negeri 3 Pagar Alam